Beta-type Ti-Nb-Zr-Cr alloys with large plasticity and significant strain hardening. (5th November 2019) - Jawed, S.F.; Rabadia, C.D.; Liu, Y.J.; Wang, L.Q.; Li, Y.H.; Zhang, X.H.; Zhang, L.C.
Abstract: A series of Ti-25Nb-8Zr-xCr (x = 0, 2, 4, 6, 8 wt%) alloys were designed based on DV-Xα cluster method and e / a ¯ - Δr ¯ diagram with an anticipation to obtain high plasticity and significant strain hardening. The designed alloys were produced through cold crucible levitation melting technique in order to effectively investigate their microstructures and mechanical properties. The addition of Cr significantly enhances the β stability in the microstructures of the Ti-25Nb-8Zr-xCr alloys. Both yield strength and hardness of the studied alloys increase due to the effect of solid-solution strengthening. By constrast, the plasticity, maximum strength and strain hardening rate are influenced by the β stability as well as the distinct deformation mechanisms. None of the alloys comprising Cr fail up to 100 kN (the load capacity used) and all show impressive plasticity (~75%) and superior maximum compressive strength (~4.5 GPa) at 100 kN. Moreover, the deformation bands, which are found around the hardness indentations, are analyzed for all the investigated alloys. The fracture behaviors of the Ti-25Nb-8Zr-xCr alloys are also studied to observe the characteristics related to crack propagation, plastic deformation and the formation of shear bands. Graphical abstract: Unlabelled Image Highlights: The microstructures of Ti-25Nb-8Zr-xCr alloys are affected by Cr addition. Both yield strength and hardness increase due to solid-solution strengthening effect. The content of Cr substantially enhances plasticity and strain hardening rate. Deformation mechanisms predicted by Bo ¯ - Md ¯ diagram are in line with that by e / a ¯ - Δr ¯ diagram for the studied alloys.